An experimental study of aluminum can recycling using fusion in induction furnace - Verran G.O.* (2008)
The present study investigates the influence of casting parameters on efficiency in aluminum can recycling using electric induction furnace. The cans were compacted in "packages" using high pressure. Initially, the flux amount was maintained constant (20 wt.%), but the temperature of the bath and melt treatment were changed. Next, using two different bath temperatures (750 and 850 °C) and melt treatment with an intensive mixture of flux in molten aluminum, flux amount was changed. The recovered aluminum was poured into permanent molds. Results were assessed computing the efficiency of the recycling process defined as a relation between the recycled and the original amount of aluminum. Chemical composition was evaluated by optical emission spectroscopy. Results indicated that the use of bath temperatures above 750 °C and flux amount of at least 10 wt.% leads to good recovery of aluminum after the recycling of cans. © 2007 Elsevier B.V. All rights reserved.